Estrous synchronization in hair sheep using a protocol based on prostaglandin + GnRH - Ávila-Castillo, Blas Rogelio (Universidad Autónoma de Tamaulipas, 2019)
The use of progestogens can contaminate the environment and animal tissue. Therefore, the use of prostaglandins F2α (PGF2α) and gonadotropin-releasing hormone (GnRH) may represent a viable alternative. The aim of the present work was to evaluate the effect of applying a dose of GnRH within the range of application of two doses of PGF2α, and compare it with protocols based on progestogens and PGF2α, commonly used in the synchronization of estrus, with respect to the pre-ovulatory peak of luteinizing hormone (LH), post-estrus progesterone concentrations, pregnancy rate, calving and prolificacy. After a pre-synchronization with a double application of PGF2α, 30 multiparous adult ewes (live weight = 45 ± 3.1 kg, body condition = 3.2 ± 0.5 units and postpartum time = 60 d to 90 d, they were randomly assigned to one of three treatments (n = 10). The ewes in Group 1: P (Control) received a single dose of 125 μg of cloprostenol via IM (intramuscular); the ewes in Group 2: FP received intravaginal sponges containing 20 mg of fluorogestone acetate for 5 d; and upon removal of the sponge, they were injected with 125 μg of cloprostenol via IM; the ewes in Group 3: GP received 50 μg of GnRH IM; and 7 d later, they were injected with 125 μg of cloprostenol. The onset of estrus was detected faster (P ≤ 0.05) in P and GP groups than in the FP group. The GP group (P ≤ 0.05) had higher concentrations of progesterone after 5 d post-estrus, compared to the P and FP groups. The pregnancy rate was not different (P > 0.05) between groups. All the synchronization protocols evaluated were similar in the effectiveness to improve the reproductive behavior in hair sheep. Therefore, the use of protocols based on the application of PGF2α is recommended due to their ease of application.